Cavell and the quest for a voice: the importance of the notion "Claim" in aesthetics and ethics - Miguens, Sofia (2021)
In this article I focus on Cavell's theme of finding one's voice, as it is articulated with reference to the philosophies of language of Wittgenstein and Austin. I start by spelling out Cavell's Wittgensteinian-Austinian view of culture as the background for his approach to aesthetics and ethics. I then set out to explore the work done by the theme in aesthetics and ethics around the notion claim. I argue that Cavell's effort to counter the pull of non-cognitivism in aesthetics and ethics, building on the notion claim, is not only illuminating of his unique way of inheriting the history of analytic philosophy but also gives us a glimpse of where and how Continental and analytic philosophy may again cross paths in the future.